2020
DOI: 10.3389/fphar.2020.00851
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Salvianolate Combined With Western Medicine on Diabetic Nephropathy: A Systematic Review and Meta-Analysis

Abstract: Background: Salvianolate, a compound mainly composed of salvia magnesium acetate, is extracted from the Chinese herb Salvia miltiorrhiza. Because of its biological activity, easy quality control and certain efficacy, salvianolate is widely used in treating ischemic cardiocerebral vascular disease, liver damage, renal injury, diabetes, and its complications. Particularly, it has potential protective effects on diabetic nephropathy (DN). Objective: This meta-analysis aimed to evaluate the efficacy and safety of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…As mentioned above, for patients with peripheral neuropathy caused by glucose metabolism disorder, the treatment method of integrated traditional Chinese and western medicine is very helpful for the rapid recovery of the patient's health [10] . From the results, it also has a significant improvement compared with the original physical condition.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned above, for patients with peripheral neuropathy caused by glucose metabolism disorder, the treatment method of integrated traditional Chinese and western medicine is very helpful for the rapid recovery of the patient's health [10] . From the results, it also has a significant improvement compared with the original physical condition.…”
Section: Discussionmentioning
confidence: 99%
“…Studies stating that participants had renal damage, but without baseline GFR, Ccr, or SCr; participants with diabetic nephropathy. These issues had been investigated in a previous study [ 13 ]; studies involving Salvia miltiorrhiza as one of several active components in a compound recipe were not included.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the dysbiosis of gut microbiota has a critical effect on DKD. Increased evidence has demonstrated that a number of natural products could improve the dysbiosis of gut microbiota in DKD [68][69][70][71][72].…”
Section: Iga Nephropathymentioning
confidence: 99%